Investigation of Antibacterial Effect of Cuminum cyminum and Carum carvi against Streptococcus mutans and Streptococcus pyogenes - Ghazi, Mona; Goudarzi, Hossein; Ataee Zadeh Ardekani, Hamidreza; Habibi, Maliheh; Azargashb, Eznolla; Hajikhani, Bahareh; Goudarzi, Mehdi (Novelty in Biomedicine, 2019)
Background: Streptococcus mutans is major cause of tooth decay. In addition, there is some report about effects of Streptococcus pyogenes on odontogenic infections. Herbal drugs is now administrating for treatment of some disease. The aim of this study was to evaluate the antibacterial effect of Cuminum cyminum and Carum carvi against Streptococcus mutans and Streptococcus pyogenes. Materials and Methods: In this study, standard strains of Streptococcus mutans and Streptococcus pyogenes were used, and ethanolic extract was prepared in the microbiological laboratory of Shahid Beheshti University of Medical Sciences. The experiment was repeated 6 times and chlorohexine 2% was used as a control. Results: The best effect of Carum carvi was on Streptococcus mutans, whereas on Streptococcus pyogenes both extracts of Cuminum cyminum and Carum carvi showed the same effect. Conclusion: This study showed, due to the fact that the Cuminum cyminum and Carum carvi extracts exhibited excellent antibacterial properties, they could be a suitable candidate in compounds such as mouthwash, toothpastes and Gums. Therefore, could be used in the prevention and treatment of future oral and dental diseases.